1968
DOI: 10.1111/j.1469-8986.1968.tb02810.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep Inspirations as Stimuli for Responses of the Autonomic Nervous System

Abstract: The effects of four types of deep breaths on the latency, the magnitude and the duration of finger volume pulse, heart rate and galvanic skin responses were studied in a quasi‐learning situation. The respiratory stimuli were normal inspirations, three times deeper than normal, six times deeper and fast, and six times deeper and slow. Twenty Ss took each type of deep breath in random order six times in response to specific lights. Graphs and statistical tests are presented summarizing the above relationships an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…If changes in sniffing behavior systematically altered the SC, an SC decrease for odors with positive names would be expected, whereas we found SC increase. Third, we observed changes elicited by odor names on SC but not on HR, and both of these physiological processes can be affected by breathing (Stern and Anschel 1968). The fact that our findings are specific to SC lends further support to the conclusion that the changes in SC observed in this study were not caused by breathing variations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…If changes in sniffing behavior systematically altered the SC, an SC decrease for odors with positive names would be expected, whereas we found SC increase. Third, we observed changes elicited by odor names on SC but not on HR, and both of these physiological processes can be affected by breathing (Stern and Anschel 1968). The fact that our findings are specific to SC lends further support to the conclusion that the changes in SC observed in this study were not caused by breathing variations.…”
Section: Discussionsupporting
confidence: 73%
“…It is well known that breathing patterns directly modify autonomic nervous system responses and that deeper breaths lead to a decrease in skin response and to an increase followed by a decrease in heart rate (HR) (Stern and Anschel 1968). Therefore it was important to exclude the possibility that sniffing patterns in the present investigation could account for any changes observed in SC.…”
Section: Discussionmentioning
confidence: 98%
“…It would appear that this effect is not readily accounted for by group differences in task performance, either in terms of the number of correct answers given or in the number of problems attempted (answers stated], since no such differences were observed. It appears unlikely that the Type A-B differences in TWA response was due to differences in respiratory activity accompanying subjects' verbalization of their answers to the experimental task, since no significant group difference in HR response was observed and HR has been found to be highly sensitive to variations in both respiration rate (17) and inspiration depth (18). The present results extend those of Van Egeren et al (7), who observed exaggerated ventricular ECG responses in Type A college students, to an older sample of employed men.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, study participants may elicit voluntary EDRs by a deep inhalation and subsequent holding of their breath (e.g., Hygge & Hugdahl, 1985). Stern and Anschel (1968) investigated the action of different respiratory patterns on the SRR amp. and on cardiovascular measures in 20 study participants.…”
Section: Physiologically Based Artifactsmentioning
confidence: 99%